2019
DOI: 10.1111/bcp.13908
|View full text |Cite
|
Sign up to set email alerts
|

Activity and mRNA expression levels of selected cytochromes P450 in various sections of the human small intestine

Abstract: Aims: To characterize mRNA expression levels (17 cytochromes P450) and activity (9 isoforms) of major cytochromes P450 expressed throughout the human small intestine.Methods: Tissue samples were obtained from 9 deceased subjects and intestinal sections (n = 10) were isolated for each subject. Relative mRNA expression levels were determined using quantitative real-time PCR. Intestinal microsomes were prepared from 5 subsections: duodenum, jejunum (proximal and mid-jejunum) and ileum (proximal and mid-ileum) reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 31 publications
9
19
0
Order By: Relevance
“…We measured significant mRNA amounts for multiple CYP450 isoforms with mRNAs of CYP2C9 and CYP3A4/5 being the most expressed. This is in agreement with several studies reporting mRNA levels or immune-quantified proteins of CYP450s in the human small intestine [16,17,18,38,39,40]. High levels of mRNA for CES-2 in duodenal biopsies for both study groups were also detected in this study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We measured significant mRNA amounts for multiple CYP450 isoforms with mRNAs of CYP2C9 and CYP3A4/5 being the most expressed. This is in agreement with several studies reporting mRNA levels or immune-quantified proteins of CYP450s in the human small intestine [16,17,18,38,39,40]. High levels of mRNA for CES-2 in duodenal biopsies for both study groups were also detected in this study.…”
Section: Discussionsupporting
confidence: 93%
“…CYP450 expression and activity profiles are tissue specific and, clearly, extra-hepatic tissues differ from the liver [8,9,10,11,12,13]. Various expression profiles for drug metabolizing enzymes and transporters have been observed along the intestinal tract [14,15,16,17]. There is a general consensus that the most highly expressed CYP450s in human intestines are CYP2C and CYP3A subfamilies [18].…”
Section: Introductionmentioning
confidence: 99%
“…CYP2J2 . CYP4F2 (Clermont et al, 2019). Gene expression results with intestinal biopsies show that PXR, CYP3A4, and villin 1 expression was decreased in the inflamed small intestinal tissue in children with Crohn's disease (Shakhnovich et al, 2016), a result consistent with that observed in hepatocytes (El-Kadi et al, 1997;Assenat et al, 2004), suggesting that environment factors may have effects on the expression of drug metabolizing enzymes in the human small intestine via similar mechanisms as observed in the human liver.…”
Section: In Vitro/ex Vivo Findingssupporting
confidence: 58%
“…Using CHIM, UGT2B7 and UGT2B17 activities further defined using isoform selective substrates and inhibitors, with significant correlation with protein abundance based on proteomics (Zhang et al, 2020). The results with the P450 isoforms with the intact cell enteric models are similar to those reported for intestinal microsomes (Clermont et al, 2019).…”
Section: In Vitro/ex Vivo Findingssupporting
confidence: 57%
“…Challenges associated with obtaining intestinal tissue samples increase the value of studies reporting the actual protein abundances as opposed to mRNA levels. There are a number of reports on mRNA expression data of genes encoding DMEs and drug transporters in the human small intestine (Thörn et al, 2005;Clermont et al, 2019;Fritz et al, 2019). However, caution should be exercised in using these values because the relationship between mRNA and protein abundance appears inconsistent (Berggren et al, 2007;Hayeshi et al, 2008), suggesting that mRNA data in a high-turnover tissue such as intestine may have limited utility for PBPK modeling.…”
Section: Introductionmentioning
confidence: 99%